2012
DOI: 10.1016/j.watres.2012.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of competitive adsorption between 2-methylisoborneol and natural organic matter on superfine and conventionally sized powdered activated carbons

Abstract: 18When treating water with activated carbon, natural organic matter (NOM) is not only a target for 19 adsorptive removal but also an inhibitory substance that reduces the removal efficiency of trace 20 compounds, such as 2-methylisoborneol (MIB), through adsorption competition. Recently, superfine 21 (submicron-sized) activated carbon (SPAC) was developed by wet-milling commercially available 22 powdered activated carbon (PAC) to a smaller particle size. It was reported that SPAC has a larger 23 NOM adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 32 publications
5
56
1
Order By: Relevance
“…The same influence of NOM on the adsorption capacity between SPAC and PAC suggests the same loading of NOM that compete with MIB for adsorption sites. Details for the effect of NOM loading on SPAC and PAC adsorption are seen elsewhere (Matsui et al, 2012). The presence of NOM also reduced the geosmin adsorption capacities of SPAC and PAC to a similar extent ( Figure 1E); as with MIB, the geosmin adsorption capacity of SPAC10 in the presence of NOM was also higher than that of PAC10.…”
Section: Equilibrium and Kinetics Of Adsorptionmentioning
confidence: 65%
See 1 more Smart Citation
“…The same influence of NOM on the adsorption capacity between SPAC and PAC suggests the same loading of NOM that compete with MIB for adsorption sites. Details for the effect of NOM loading on SPAC and PAC adsorption are seen elsewhere (Matsui et al, 2012). The presence of NOM also reduced the geosmin adsorption capacities of SPAC and PAC to a similar extent ( Figure 1E); as with MIB, the geosmin adsorption capacity of SPAC10 in the presence of NOM was also higher than that of PAC10.…”
Section: Equilibrium and Kinetics Of Adsorptionmentioning
confidence: 65%
“…The sample was transported in polyethylene tanks and stored at 4 °C. The water was filtered through a 0.2-µm-pore membrane (DISMIC-25HP; Toyo Roshi Kaisha, Tokyo) and diluted to adjust the dissolved organic carbon concentration to ~1.5 mg/L; the diluent used for this purpose was prepared by amending ultrapure water (Milli-Q Advantage, Millipore Co.) with salts to obtain an ionic composition similar to that used in a previous study (Matsui et al, 2012). Stock solutions of MIB and geosmin were prepared by dissolving the pure chemicals (Wako Pure Chemical Industries, Osaka, Japan) in ultrapure water.…”
Section: Water Samplesmentioning
confidence: 99%
“…Once the available adsorption sites are filled the removal efficiency is significantly diminished. Common granular activated carbon (GAC) materials are comprised primarily of micropores (>1 nm) which are highly effective at adsorbing dissolved contaminants, but are easily blocked by suspended solids (Matsui et al, 2012). The development of a bacterial biofilm can aid in the bioregeneration of adsorption sites but this is also limited and eventually the carbon material will need to be replaced (Simpson, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the biological degradation of geosmin and MIB is anticipated with the application of bioflocs. In addition, the biodegradation of geosmin and MIB has been demonstrated in active carbon filters (Elhadi et al 2004;Matsui et al 2012) and sand filers (Ho et al 2007;McDowall et al 2009). However, in the present study, biodegradation was found to be less important than chemical/physical sorption in the overall removal of geosmin and MIB under in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%